The effect of play supported program on the school readiness of 60-72 month-old disadvantaged children - (:unkn) unknown (Sakarya University, 2015)
The aim of this research is to examine the effect of The Play supported Program designed for 60-72 month-old disadvantaged children on their readiness levels. The sample of the research has consisted of an experimental group and a control group, each having twenty 60-72 months old children (10 girls and 10 boys) at Göztepe Semiha Şakir Children’s Home, an institution under the Turkish Republic Social Services and Society for the Protection of Children in Kadıköy Istanbul during 2010-2011 Academic Year. Research was designed according to pretest-posttest control group model. The Play Supported Program was prepared for the 60-72 month-old disadvantaged children and the training program has been carried out with the experimental group. The control group was not given an extra program. The development and application forms of “Marmara Primary School Education Readiness Scale”, which was developed and standardized by Polat Unutkan in 2003, have been used to gather data in the research. The results of the research show that there are significant differences in the favor of experiment group on the aspects of Mathematics, Science, Audio Capabilities, Cognitive and Language Development, Social and Emotional Development, Physical Development, and Self-Care Skills. © 2015, The Turkish Online Journal of Educational Technology.
Keywords: Disadvantaged Children; Play Supported Program of School Readiness; School Readiness; Social Services and Society for the Protection of Children